The enactment of moderation in Plato's "Charmides" - Press, Gerald A. (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Plato’s dialogues are as much literary dramas as philosophical inquiries. In light of the scope and development of σωφροσύνη and the carefully crafted historical resonances of the dialogue’s dramatic date and cast of characters, it is argued here that σωφροσύνη is a foundational virtue, best understood as moderation, moderating one’s behavior, rather than on a par with other virtues. The Charmides is non-dogmatic, rather than skeptical or aporetic, and essentially political rather than ethical or epistemological, as often assumed. Rather than asserting any simple, propositional account of moderation, it enacts a complex moral and political view of moderation that unifies many strands of the term’s meanings in Greek through the persons and words of its characters and operating as much through the reader’s, imagination, and emotions as through reason and purely logical argument.